PENERAPAN STRATEGI THE POWER OF TWO UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA SISWA KELAS X SMAN 9 PEKANBARU - Hanifli Hanifli (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low activity of learning mathematics class X SMAN 9 Pekanbaru. This study aims to increase the activity of learning mathematics class X SMAN 9 Pekanbaru with the implementation of strategy the power of two. The subjects were all students of grade X SMAN 9 Pekanbaru totaling 34 people, in the academic year 2015/2016. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the results of research and discussion can be concluded that the strategy implementation power of two can increase the activity of learning mathematics students in the class X SMAN 9 Pekanbaru in the first semester of the 2015/2016 academic year. Although implementation of the strategy is a power of two can increase the activity of learning mathematics in grade X SMAN 9 Pekanbaru it is seen as the first cycle reaching an average of 60.5% and increased in the second cycle to 78%, this was successful because it exceeds 75%.